Risks of Bitcoin Virtual Currency - Cekerevac, Zoran; Dvorak, Zdenek; Prigoda, Ludmila; Cekerevac, Petar (Communications - Scientific letters of the University of Zilina, 2015)
Bitcoin, digital money got into focus after the Mt Gox crash. It uses P2P interaction where an owner transfers the electronic coin to the next owner signing and adding a hash of the previous transaction and the public key of the next owner. Payment verification is accomplished by notifying the entire network about the transaction. This prevents double-spending and generation of non-existent money. Among the users, there is uncertainty about the safety on the theft and fraud. Among the authorities, there are dilemmas about present and future risks related to the Bitcoin implementation. The article deals with the benefits and risks of Bitcoin use.